DIGITAL IMAGES EDGE DETECTION USING MATHEMATICAL MORPHOLOGY OPERATIONS - Ali, Hanaa (Iraqi Journal of Science, 2024)
The field of mathematical morphology contributes a wide range of operators to image processing, all based around a few simple mathematical concepts from set theory. The two most basic operations in mathematical morphology are erosion and dilation, both of these operators take two pieces of data as input; an image to be eroded or dilated, and a structuring element. Opening and closing are two important operators from mathematical morphology; they are both derived from the fundamental operations of erosion and dilation. The primary application of mathematical morphology in this work occurs in binary images throw applying erosion and dilation operations to extract boundary edges, and then basic morphology operations are adopted to grey level images which are erosion residue and morphological gradient in order to achieve image edges detection.